1999
DOI: 10.1002/(sici)1097-4628(19990801)73:5<777::aid-app18>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion polymerization of tetrafluoroethylene: effects of reaction conditions on the polymerization rate and polymer molecular weight

Abstract: ABSTRACT:The emulsion polymerization of tetrafluoroethylene (TFE) was carried out in a semibatch reactor using a chemical initiator (ammonium persulfate) and a fluorinated surfactant . The effects of the reaction condition were investigated though the polymerization rate, molecular weight of polytetrafluoroethylene (PTFE), and stability of the dispersion. The emulsion polymerization of TFE was different from conventional emulsion polymerization. The polymerization rate was suppressed when the polymer particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…No articles could be found in the literature that set down reactor-independent correlations for the polymerization rate in terms of fundamental polymerization rate constants of TFE. The polymerization rates reported by Kim et al, Xu et al, Lai et al, etc., as well as all the patent literature, are lumped terms that include reactor hydrodynamics as well as diffusion effects. Significant research scope exists for determining the kinetics of polymerization and, in particular, the effects of temperature and pressure on the dispersity of PTFE.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…No articles could be found in the literature that set down reactor-independent correlations for the polymerization rate in terms of fundamental polymerization rate constants of TFE. The polymerization rates reported by Kim et al, Xu et al, Lai et al, etc., as well as all the patent literature, are lumped terms that include reactor hydrodynamics as well as diffusion effects. Significant research scope exists for determining the kinetics of polymerization and, in particular, the effects of temperature and pressure on the dispersity of PTFE.…”
Section: Discussionmentioning
confidence: 93%
“…Other configurations reported include unbaffled reactors with anchor-type agitators and horizontal reactors with paddle-type agitators (these are mostly used in copolymerization). Kim et al investigated the efficacy of various stirrer types for TFE polymerization and found that vortex formation and the maximization of gas-to-liquid surface area are the most important criteria to look at when selecting a stirrer. They recommend the use of an anchor-type stirrer with a baffled tank.…”
Section: Polymerization Process and Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Early reports by Ziegler and coworkers of metal-catalyzed alkene polymerization promoted by Et 2 AlCl have evolved 5 decades later to a tour de force of organometallic chemistry with molecular control of polypropylene tacticity, living catalysts for block co-polymer formation, and late metal chain-walking as only three of many highlights [23][24][25]. In contrast, polymerization of fluoroalkenes traditionally utilizes radical processes, either in the gas phase or in aqueous emulsions [26][27][28][29]. As a result, while the properties of fluoropolymers can be tuned by altering reaction conditions or changing the relative amounts of co-monomers, attempts at molecular control have met with little success.…”
Section: Introductionmentioning
confidence: 99%